The Ertebølle Zooarchaeological Dataset from Southern Scandinavia. (6th January 2016) - Gron, Kurt J.; Robson, Harry K.
Interdisciplinary archaeological research in southern Scandinavia has a long history of practice, beginning in the mid-19 th century. In particular, research concerning the late Mesolithic hunter-gatherer-fisher Ertebølle culture (5400-3950 cal BC) has resulted in a large zooarchaeological dataset useable in large-scale comparative or meta-analyses. In this paper, we review this dataset, and the quantity and character of the data is described. We then address particularities of the published data that may affect comparative analyses. By focusing on fragmentation and bone condition as major influencing factors on published quantitative statistics, we demonstrate that caution is warranted in comparisons between these types of data deriving from Ertebølle assemblages. Nevertheless, we focus on the dataset as a valuable resource for understanding variability in hunter-gatherer-fisher food economies and how to best mitigate potential issues in selection and use of the data in comparative studies. We do so by discussing types of comparative analyses that are most likely to provide valuable information about the human past. Lastly, we propose a series of recommendations that should inform and ensure the comparability of future Ertebølle research, and present our review as a case study in zooarchaeological meta-analyses.